Status of emergency obstetric care in six developing countries five years before the MDG targets for maternal and newborn health. - Charles Ameh (Public Library of Science (PLoS), 2012)
Background Ensuring women have access to good quality Emergency Obstetric Care (EOC) is a key strategy to reducing maternal and newborn deaths. Minimum coverage rates are expected to be 1 Comprehensive (CEOC) and 4 Basic EOC (BEOC) facilities per 500,000 population. Methods and findings A cross-sectional survey of 378 health facilities was conducted in Kenya, Malawi, Sierra Leone, Nigeria, Bangladesh and India between 2009 and 2011. This included 160 facilities designated to provide CEOC and 218 designated to provide BEOC. Fewer than 1 in 4 facilities aiming to provide CEOC were able to offer the nine required signal functions of CEOC (23.1%) and only 2.3% of health facilities expected to provide BEOC provided all seven signal functions. The two signal functions least likely to be provided included assisted delivery (17.5%) and manual vacuum aspiration (42.3%). Population indicators were assessed for 31 districts (total population = 15.7 million). The total number of available facilities (283) designated to provide EOC for this population exceeded the number required (158) a ratio of 1.8. However, none of the districts assessed met minimum UN coverage rates for EOC. The population based Caesarean Section rate was estimated to be <2%, the maternal Case Fatality Rate (CFR) for obstetric complications ranged from 2.0-9.3% and still birth (SB) rates ranged from 1.9-6.8%. Conclusions Availability of EOC is well below minimum UN target coverage levels. Health facilities in the surveyed countries do not currently have the capacity to adequately respond to and manage women with obstetric complications. To achieve MDG 5 by 2015, there is a need to ensure that the full range of signal functions are available in health facilities designated to provide CEOC or BEOC and improve the quality of services provided so that CFR and SB rates decline.